The Concept of Islamization of Knowledge According to Syed Muhammad Naquib Al Attas and Its Relevance to Contemporary Islamic Education - Sidqi Ali; Shinta Adhelia Putri Sugiharto; Nasrulloh (Penerbit Presisi Pustaka, 2025)
This study examines Syed Muhammad Naquib al-Attas’s concept of the Islamization of knowledge and its relevance to contemporary Islamic education. The growing influence of secularization in modern education has caused a significant epistemological crisis in the Muslim world, where knowledge has become separated from its divine purpose and spiritual orientation. Using a qualitative library research method, this article analyzes al-Attas’s major works including Islam and Secularism (1978), The Concept of Education in Islam (1980), and Prolegomena to the Metaphysics of Islam (1995) alongside relevant scholarly sources. The findings indicate that al-Attas frames Islamization as an epistemological process aimed at purifying knowledge from secular Western assumptions and restoring it within a tawhidic worldview. Central to this process is the formation of insān ādīb, a well-educated and virtuous individual who integrates intellect, faith, and ethical discipline. In the context of contemporary Islamic education, this concept provides a critical response to the dichotomy between religious and secular sciences and encourages an integrative paradigm that unites reason, revelation, and morality. Therefore, the Islamization of knowledge not only addresses the modern crisis of meaning in education but also offers a coherent philosophical foundation for reconstructing Islamic educational systems toward a holistic and God-centered orientation.